Pengaruh Waktu dan Frekuensi Aplikasi Pupuk Daun Terhadap Pertumbuhan dan Pembungaan Anggrek Dendrobium ’Tong Chai Gold’ - Dewi Sukma; Ary Setiawati (Jurnal Hortikultura Indonesia, 2010)
ABSTRACTMost of orchids grow slowly. Low fertilizer concentration with high frequency of fertilization can be the alternative to increase orchids growth. The objective of the research was to evaluate the effect of time and frequency of fertilizer application on Dendrobium ‘Tong Chai Gold’. The experiment was arranged in randomized of completely block design with two factor of treatment. The first factor is time of application and the second one is frequency of application of foliar fertilizer. The time applications in the morning about 6.30 to 7.30 o’clock, at mid day about 11.30 to 12.30 o’clock, and in the afternoon about 16.30 to 17.30 o’clock. The frequency of foliar fertilizer application were every three days or six days. The result of this experiment showed that time and frequency application of foliar fertilizer could not increased number of bulb, but increased young leaf length, and width. Fertilizer was applied in the morning combined with every three days frequency of fertilizer tended to result a better flowering of Dendrobium ‘Tong Chai Gold’.Key words : Dendrobium, fertilizer, application time and frequency, growth, flowering,